2008
DOI: 10.1128/iai.01291-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes in Mycoplasma hyopneumoniae during Infection

Abstract: Mycoplasma hyopneumoniae causes swine pneumonia and contributes significantly to the porcine respiratory disease complex. The mechanisms of pathogenesis are difficult to address, since there is a lack of genetic tools, but microarrays are available and can be used to study transcriptional changes that occur during disease as a way to identify important virulence-related genes. Mycoplasmas were collected from bronchial alveolar lavage samples and compared to broth-grown cells using microarrays. Bronchial alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
0
32
2
Order By: Relevance
“…Gene expression profiling has been intensively used for several mycoplasma species to study host-pathogen interactions. In this context, the transcriptomes of either the host or the pathogen were investigated to gain further insights into mycoplasma-induced pathogenesis [4044]. To the best of our knowledge this is a singular study in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling has been intensively used for several mycoplasma species to study host-pathogen interactions. In this context, the transcriptomes of either the host or the pathogen were investigated to gain further insights into mycoplasma-induced pathogenesis [4044]. To the best of our knowledge this is a singular study in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the direction of regulation of differentially expressed genes in norepinephrine-exposed M. hyopneumoniae to those genes shown to be differentially expressed under heat shock (Madsen et al, 2006a), iron deprivation (Madsen et al, 2006b), oxidation conditions (Schafer et al, 2007) and in vivo growth (Madsen et al, 2008), an interesting correlation was observed. Genes upregulated during norepinephrine exposure were generally downregulated under the other conditions, if at all (Supplementary Table S1).…”
Section: Interpretation Of the Differential Responsesmentioning
confidence: 97%
“…There is also a large group of transport-related proteins that might be involved and serve as receptors. Finally, given the diversity of genes regulated under different environmental conditions such as heat shock (Madsen et al, 2006a), iron deprivation (Madsen et al, 2006b), oxidative stress (Schafer et al, 2007) and the pig lung (Madsen et al, 2008), transcription in M. hyopneumoniae must involve multiple factors and mechanisms. We are only beginning to decipher those components and their mechanisms of action (Chang et al, 2008).…”
Section: Interpretation Of the Differential Responsesmentioning
confidence: 99%
“…However, these studies were unable to identify genes specifically related to virulence, even when analysing the infection conditions [13]. The M. hyopneumoniae proteomic studies performed thus far were mainly prospective.…”
Section: Introductionmentioning
confidence: 99%